Assessment of the Implementation of the Religious Character Strengthening Programe - Santoso Santoso; Tomi Hidayat; Pariyanto Pariyanto (Postgraduate, University of Mataram, 2023)
The purpose of this research is to assess the implementation of the strengthening of religious character education (PPK) at SMK Negeri 7 Bengkulu Utara. This research is an evaluative research with a descriptive approach. The population involved in the implementation of KDP are: principals, teachers and students. The research sample consisted of the principal, vice principal for curriculum affairs, five representatives of the teacher council and 92 students. Data collection techniques using a questionnaire. The data analysis technique used statistical analysis of percentages. The results of this study indicate that: the implementation of strengthening religious character education in SMK Negeri 7 Bengkulu Utara in general has good criteria with the level of program implementation reaching 73.21%.